2003
DOI: 10.1097/00126334-200312150-00004
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Selective Neuronal Damage in Methamphetamine-User AIDS Patients

Abstract: The risk for HIV infection attributable to methamphetamine (METH) use continues to increase. The combined effect of HIV and METH in the pathogenesis of HIV encephalitis (HIVE) is unclear, however. To better understand the neuropathology associated with HIV and METH use, the patterns of neurodegeneration were assessed in HIV-positive METH users and in HIV-positive non-METH users. Patients in the study met criteria for inclusion and received neuromedical and postmortem neuropathologic examinations. Immunocytoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(98 citation statements)
references
References 40 publications
3
94
1
Order By: Relevance
“…Similarly, methamphetamine exposure causes neurotoxicity in mesolimbic and mesocortical brain regions (Mark et al, 2004). Individuals who are both methamphetamine dependent and HIV+ show exacerbated neuronal injury (Chang et al, 2005) and cortical interneuron loss (Langford et al, 2003;Chana et al, 2006), which may also contribute to impaired cognitive performance. The role of specific HIV-associated products that could contribute to the interactive effects of methamphetamine and HIV on learning and executive functions is less understood.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, methamphetamine exposure causes neurotoxicity in mesolimbic and mesocortical brain regions (Mark et al, 2004). Individuals who are both methamphetamine dependent and HIV+ show exacerbated neuronal injury (Chang et al, 2005) and cortical interneuron loss (Langford et al, 2003;Chana et al, 2006), which may also contribute to impaired cognitive performance. The role of specific HIV-associated products that could contribute to the interactive effects of methamphetamine and HIV on learning and executive functions is less understood.…”
Section: Introductionmentioning
confidence: 99%
“…HIV-positive individuals might experience greater harm from methamphetamine use than HIV-uninfected individuals. 28,29 Given the reports of HAART nonadherence related to methamphetamine use, 30,31 they are also at increased risk for missing medication doses, which has been shown to increase HIV viral load. 39,40 Because these persons are in medical care and report high comfort levels discussing their experiences with providers, they are excellent candidates for frank, open discussion of sexual risks and substance abuse as recommended by the Centers for Disease Control (CDC) and others.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 HIV-positive individuals incur direct harm from methamphetamine that has been shown to hasten HIV dementia 28 and selectively damage dopaminergic central-nervous system neurons in HIV-infected individuals. 29 Methamphetamine also interferes with adherence to highly active antiretroviral therapy (HAART) as a result of patient concerns about methamphetamine-HAART interactions (planned nonadherence) and forgetting to take HAART while under the influence of methamphetamine (unplanned nonadherence). 30 Increased HIV viral loads because of HAART nonadherence has been described among persons using methamphetamine.…”
Section: Introduction Mmentioning
confidence: 99%
“…Imaging studies have revealed reduced hippocampal volume and greater damage to frontal cortex interneurons in HIV-positive methamphetamine users as compared with control groups [76,[82][83][84]. Reduced Nacetyl aspartate in the anterior cingulate has also been observed [85].…”
Section: Methamphetaminementioning
confidence: 98%